A note on automorphisms of halved Cayley graphs of Coxeter systems - Pankov, Mark (Ars mathematica contemporanea, 2016)
We consider the halved Cayley graphs of Coxeter systems and show that every automorphism of such a graph can be uniquely extended to an automorphism of the corresponding Cayley graph.
Keywords: Cayley graph; Cayleyjev graf; Coxeter system; Coxeterjev sistem